Impact of Home Oxygen Therapy on the Level of Physical Activities in Daily Life in Subjects With COPD - Cani, Katerine C; Matte, Darlan L; Silva, Isabela J C S; Gulart, Aline A; Karloh, Manuela; Mayer, Anamaria F (Respiratory care, 2019)
Chronic hypoxemia in patients with COPD is a limiting factor that is associated with disease progression and significantly contributes to decreased physical activity. Although correction of hypoxemia results in physiological improvements, oxygen therapy may be related to social isolation and inactivity. However, few studies have objectively investigated the level of physical activity in daily life (PADL) in these patients. The objective of this study was to compare the level of PADL in subjects with COPD on home oxygen therapy and in subjects with no oxygen therapy, and to investigate whether home oxygen therapy is associated with the level of PADL. In this study, 29 subjects with COPD composed the home oxygen therapy group, and 30 subjects with COPD composed the control group. All of them underwent assessment of anthropometric measurements, spirometry, peripheral muscle strength, limitations in activities of dalily living, perception of dyspnea, health status, as well as PADL monitoring. Home oxygen therapy subjects showed less time walking ( = .001), in active physical activities ( = .003), in physical activities ≥ 3 METs ( = .001), and in physical activities < 1.5 METs ( = .042), as well as fewer steps ( = .001). Physical inactivity was present in 24 home oxygen subjects (82.8%) and 18 control subjects (60%). Oxygen therapy was associated with severe physical inactivity (Cramer's V = 0.29, = .040). The time using oxygen therapy (h/d) was the strongest predictor of the level of PADL (r = 0.38-0.43, < .001). Subjects with COPD using oxygen at home showed reduced level of PADL. The results indicate that oxygen therapy is associated with severe physical inactivity and may be a predictor of the level of PADL.